Effect of echoendoscope angle on success of guidewire manipulation during endoscopic ultrasound-guided hepaticogastrostomy - Ogura, Takeshi; Nishioka, Nobu; Ueno, Saori; Yamada, Tadahiro; Yamada, Masanori; Imoto, Akira; Hakoda, Akitoshi; Higuchi, Kazuhide (Endoscopy, 2020)
Background With endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS), guidewire manipulation might be a critically limiting step for nonexperts. However, the causes of difficult guidewire manipulation remain unclear. The aim of this study was to evaluate factors associated with successful guidewire manipulation.Methods This retrospective cohort study included consecutive patients who underwent EUS-HGS between October 2018 and October 2019. We measured scope angle between the long and needle axes of the echoendoscope using still fluoroscopic imaging immediately after puncturing the intrahepatic bile duct. Factors associated with successful guidewire insertion were assessed by multivariable analysis using logistic regression.Result The influence of the angle between the fine-needle aspiration (FNA) needle and echoendoscope on failed guidewire insertion was assessed using receiver operating characteristic (ROC) curves. Area under the ROC curve was 0.86 (95 % confidence interval [CI] 0.00 – 0.76), and an angle of 135° offered 88.0 % sensitivity and 82.9 % specificity for predicting successful guidewire insertion. According to multivariable analysis, only angle between the FNA needle and echoendoscope > 135° was independently associated with successful guidewire insertion (odd ratio 0.03, 95 %CI 0.01 – 0.14; P < 0.05), whereas sex, puncture site, and diameter of puncture site were not significant factors. After multivariable analysis, all variables were adjusted using age ≥ 70 or < 70 years, yielding the same results.Conclusion The angle between the FNA needle and echoendoscope might be associated with successful guidewire manipulation during EUS-HGS. Adjusting this angle to 135° before puncturing the intrahepatic bile duct might be helpful in achieving successful guidewire manipulation during EUS-HGS.